Investigation of red substances applied to chank shell beads from prehistoric site of Qulong in Ngari Prefecture, Tibet, China - Wang, Juan; Zhang, Baoshuai; Xi, Lin; Hu, Songmei; Zhang, Yuanyuan; Fan, Anchuan (Frontiers in Earth Science, 2023)
“Applying red” is a common phenomenon observed in Chinese archaeological sites, with the red pigments having been identified as red ochre or cinnabar if ever been scientifically analyzed. However, this is not the case for Tibet. Although a relatively large number of red-painted artifacts have been recovered in Tibet dating from the Neolithic Period to the Tubo Dynasty, little effort has been made on the pigment composition. Recently, nearly one hundred red substances covered shell beads made of the scared chank (Turbinella pyrum), a large conch from the Indian Ocean, were unearthed from the Qulong site (c. 800–500 BC) in the Ngari plateau, western Tibet. This shell beads assemblage represents the largest and most concentrated group of chank shell beads recovered in the Tibetan Plateau and its surrounding regions. It provides a crucial clue for exploring the local “applying red” tradition. In this study, eight shell beads excavated from the Qulong site were examined by the Portable Energy-dispersive X-ray Fluorescence Spectrometer (pXRF), X-ray diffraction (XRD), Fourier Transform infra-red spectroscopy (FTIR), and Laser Raman spectroscopy. The results are as follows: 1) the coloring agent of all red pigments on the shell bead is iron oxide, i.e., red ocher; 2) bone powder that has not been heated to high temperatures (above 600°C) and proteinaceous binders were added to the paint on the outer surface of sample QSM1-11a, but the thin layer on its interior surface was without bone powder; 3) bone powder was not added to the red residues on samples other than QSM1-11a, QSM1-13b, and QSM2-12. This research may reveal the complexity and diversity of the red substances applied to shell beads from Qulong, and shed light on our understanding of human practices and local customs in the Tibetan plateau and the surrounding areas in prehistoric times.